Increased reporting of interstitial pneumonitis with combined EGFR-TKI and PD-1/PD-L1 inhibitor therapy in NSCLC: a pharmacovigilance analysis of 67,818 reports - Jinyi Tao; Zhiwen Fu (Frontiers in Immunology, 2026)
Importance Both epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and PD-1/PD-L1 inhibitors are widely used in non–small cell lung cancer (NSCLC). The safety of their combination, particularly the risk of interstitial pneumonitis (IP), remains unclear but has critical implications for treatment strategies. Objective To evaluate reporting patterns of IP associated with EGFR-TKI monotherapy, PD-1/PD-L1 inhibitor monotherapy, and their combination among NSCLC cases. Design Retrospective, observational pharmacovigilance study using reports from the US Food and Drug Administration Adverse Event Reporting System (FAERS) submitted from January 1, 2015, to December 31, 2024. Multivariable logistic regression was applied to estimate adjusted odds ratios (aORs) with 95% CIs. Setting Spontaneous adverse event reporting system capturing voluntary reports submitted globally by healthcare professionals, patients, and manufacturers; it is not a population-based registry, and the total number of patients exposed to each drug is unknown. Participants A total of 67,818 NSCLC-related FAERS reports were identified, including 13,678 reporting EGFR-TKI monotherapy, 30,722 reporting PD-1/PD-L1 inhibitor monotherapy, and 307 reporting co-reported combination therapy. Reports were included if they indicated NSCLC and exposure to at least one EGFR-TKI or PD-1/PD-L1 inhibitor. IP was defined using standardized MedDRA preferred terms. Results Among 67,818 NSCLC reports, 3,970 (5.85%) included IP-related preferred terms. The reporting proportions were 4.88% (668/13,678) for EGFR-TKIs, 10.59% (3,254/30,722) for PD-1/PD-L1 inhibitors, and 15.64% (48/307) for combination therapy. Compared with EGFR-TKIs, PD-1/PD-L1 inhibitors were associated with higher adjusted reporting odds (aOR, 1.77; 95% CI, 1.60–1.96), and combination therapy showed the highest adjusted reporting odds (aOR, 3.46; 95% CI, 2.46–4.88). Agent-specific variation was observed: durvalumab plus EGFR-TKI (IP reporting proportion, 47.22%; aOR, 16.58; 95% CI, 7.89–35.51) and nivolumab plus EGFR-TKI (IP reporting proportion, 21.05%; aOR, 4.26; 95% CI, 2.57–6.79) showed the highest reporting odds, whereas pembrolizumab plus EGFR-TKI (3.85%) and atezolizumab plus EGFR-TKI (5.06%) did not show significantly increased reporting odds; these small combination subgroups are exploratory. Conclusions and relevance In this large FAERS-based pharmacovigilance analysis, combination therapy with EGFR-TKIs and PD-1/PD-L1 inhibitors was associated with markedly increased reporting of IP, with apparent heterogeneity across agents. As a spontaneous-reporting study without a defined denominator, these findings reflect a reporting association and safety signal rather than a confirmed clinical risk estimate. They support continued pharmacovigilance and prospective studies to clarify the safety of combining these therapies in NSCLC.